EFEKTIVITAS PENGELOLAAN DANA BOS BERBASIS PRINSIP SYARIAH DALAM MENDUKUNG KEGIATAN PEMBELAJARAN DI MI ROBITHOH ISLAMI GANTUNGAN - Zaenal Maarif; M Masrukhan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the effectiveness of Sharia-based management of BOS (School Operational Assistance) funds in supporting learning activities at MI Robithoh Islami Gantungan. As one of the primary funding sources for schools, BOS funds require transparent, accountable, and Sharia-compliant management to ensure their optimal impact on education quality. The research employs a quantitative approach supported by descriptive qualitative data. Primary data were collected through interviews, observations, and questionnaires, while secondary data were obtained from financial documents and academic reports of the school. The findings reveal that the implementation of Sharia principles in managing BOS funds has enhanced the efficiency of fund utilization, supported the provision of learning facilities and infrastructure, and improved students' motivation and achievements. Success indicators include better student learning outcomes, improved learning facilities, and the implementation of relevant educational programs. However, challenges remain, particularly regarding the limited understanding of Sharia principles among managers and the optimization of financial management. The study concludes that Sharia-based management of BOS funds can positively impact the quality of learning when conducted with careful planning, transparent implementation, and regular evaluation. It provides strategic recommendations for other Islamic schools to adopt similar principles in managing educational funds.